KARAKTERISTIK PASIEN PALSI SEREBRAL DI RUMAH SAKIT HAJI MEDAN TAHUN 2020-2021 - AFDILA SANDI TANJUNG; NURCAHAYA SINAGA (JURNAL ILMIAH SIMANTEK, 2022)
Cerebral Palsy is a permanent disorder that occurs in motor cells in the central nervous system that occurs early in brain development and is non-progressive. This condition can occur in the prenatal, natal, and postnatal periods. Cerebral palsy is a major cause of child disability that affects developmental function. To determine the characteristics of cerebral palsy patients at the Medan Haji Hospital in 2020-2021. This research is descriptive with a cross sectional approach. The study was conducted in October – Desember 2021. From 70 children with cerebral palsy, 55 children with cerebral palsy were found as research samples that met the inclusion criteria. The most common findings were cerebral palsy with motor spastic clinical (96.4%), clinical topographic quadriplegia (74.5%), in the age range of 1-5 years (60.0%), female (50.9%) and male. male (49.1%), the most nutritional deficiency status was malnutrition (45.5%), the most common etiology was brain infection (45.5%), the most comorbid disease was epilepsy (56.4%), and the most treatment was physiotherapy with drugs (65.5%). Conclusion: Cerebral Palsy is a non-progressive permanent brain disorder that occurs early in brain development. The most common type was spastic quadriplegia, age range 1-5 years, poor nutritional status, the most common etiology was brain infection, and the most common comorbidity was epilepsy.